Alfatoxigenic Aspergillus: current taxonomic focus - Arrúa Alvarenga Andrea Alejandra; Moreno Martínez Ernesto; Quezada Viay, Martha Yolanda; Moreno Lara, Josefina; Vázquez Badillo Ernesto; Flores Olivas, Alberto (Revista Mexicana de Ciencias Agrícolas, 2018)
The genus Aspergillus has been studied for centuries due to its industrial and deterioration properties, and its effects on health. Its identification at a genus level is relatively simple, yet at a level of species it becomes more complicated, due to the similarities between both. Due to this, taxonomists currently recommend a polyphasic focus that includes, not only morphologic characteristics, but also biochemical and molecular characteristics. The aim of this investigation was to present the basic aspects concerning the polyphasic identification of these species.